2017
DOI: 10.3399/bjgp17x692513
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ knowledge, use, and confidence in national physical activity and health guidelines and tools: a questionnaire-based survey of general practice in England

Abstract: The majority of GPs in England (80%) are unfamiliar with the national PA guidelines. Awareness of the recommended tool for assessment, GPPAQ, is higher than use by GPs. This may be because it is used by other clinical staff, for example, as part of the NHS Health Check programme. Although brief advice in isolation by GPs on PA will only be a part of the behaviour change journey, it is an important prompt, especially if repeated as part of routine practice. This study highlights the need for significant improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 19 publications
6
129
0
Order By: Relevance
“…20 Doctors.net.uk has been widely used in academic surveys of doctors. 21,22 Doctors received an email invitation to participate in the survey based on their demographic and professional characteristics as collected by Doctors.net.uk. Invitations were sent until 500 primary-care and 500 secondary-care doctors were recruited.…”
Section: Survey Samplementioning
confidence: 99%
“…20 Doctors.net.uk has been widely used in academic surveys of doctors. 21,22 Doctors received an email invitation to participate in the survey based on their demographic and professional characteristics as collected by Doctors.net.uk. Invitations were sent until 500 primary-care and 500 secondary-care doctors were recruited.…”
Section: Survey Samplementioning
confidence: 99%
“…Yet national levels of PA remain static with 38% of the population failing to achieve the recommended level of PA 13 . Studies have demonstrated low levels of knowledge of PA guidelines across the population, including in working age adults 14 and healthcare professionals who have a role in encouraging people to become more active 15,16 . It may be more influential to target social norms instead of knowledge of guidelines rather than raising awareness of personal moderate or vigorous intensity PA behaviour 17 .…”
Section: Pa Guidelines and Pa Levels In Englandmentioning
confidence: 99%
“…For example, despite the unequivocal importance of physical activity, nutrition, smoking cessation and healthy weight management guidance during pregnancy-variables that obviously affect multi-generational health-research from North America and Australia shows that relatively few women receive lifestyle guidelines from physicians [72][73][74]. Discussions of physical activity in primary care and awareness of specific physical activity guidelines is very low [75]. Studies have shown that despite obesity prevalence and the obvious need for health education, approximately 60% of visits by obese patients involve a complete absence of physician engagement with lifestyle counseling/health education [76]; despite evidence showing that the adoption of a healthy lifestyle following a cancer diagnosis is linked with better long-term outcomes, the personal beliefs of physicians (that is, not believing lifestyle would affect outcomes) diminishes the likelihood of lifestyle counseling [77].…”
Section: Lifestyle In Training and Practicementioning
confidence: 99%